2001
DOI: 10.4049/jimmunol.167.4.2282
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Functional Consequences and Signal Transduction Induced by IL-3, IL-5, and Nerve Growth Factor in Human Basophils

Abstract: Previous studies have indicated a redundancy in the effects of the cytokines, IL-3, IL-5, and nerve growth factor (NGF) on acute priming of human basophils. In the current study, we have examined the effects of these three cytokines on 18-h priming for leukotriene C4 generation, their ability to induce FcεRIβ mRNA expression, or their ability to sustain basophil viability in culture. We also examine a variety of the signaling steps that accompany activation with these cytokines. In contrast with the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 55 publications
6
55
0
1
Order By: Relevance
“…Stimulation of the basophils with IL-3 was confirmed to induce a rapid, dose-dependent and sustained phosphorylation of STAT5 that peaks after 10-20 min and remains on plateau for over 1 h (25). However, as expected, this was not associated with degranulation of the cells (as assessed by the upregulation of CD63) (29,30).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Stimulation of the basophils with IL-3 was confirmed to induce a rapid, dose-dependent and sustained phosphorylation of STAT5 that peaks after 10-20 min and remains on plateau for over 1 h (25). However, as expected, this was not associated with degranulation of the cells (as assessed by the upregulation of CD63) (29,30).…”
Section: Discussionsupporting
confidence: 59%
“…Traditionally, analysis of signaling in human basophils and mast cells has been performed using Western blot techniques (18,25). Recently, it has been demonstrated that flow cytometry can generate qualitative results concerning dose responses and kinetics of signaling molecules similar and complementary to the data obtained with blotting techniques (19,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from our and other laboratories have established that IL-3 stimulates various aspects of basophil functions, such as mediator release (21,22) and in vitro survival (23,24). Furthermore, our earlier study using Boyden chamber systems demonstrated that IL-3 potently enhances in vitro locomotive responses by basophils (11).…”
Section: Basophil Tem By Il-3mentioning
confidence: 85%
“…We and others have demonstrated that IL-3 represents the most potent basophil-activating cytokine and stimulates various aspects of basophil functions, including mediator release (21,22), survival (23,24), motility (11), adhesiveness to the endothelium (14), and expression of activation markers (14). Our present finding that IL-3 potentiated basophil TEM broadens the current concept of the capacity of IL-3 to modulate allergic inflammatory responses by up-regulating basophil functions.…”
Section: Figurementioning
confidence: 99%